The Effect of Peer Support, Authoritary Parenting Style, Resilience on The Academic Achievement of Students of State Senior High School 1 Tambun - Cholidah, Nur (International Journal of Social Science, Education, Communication and Economics, 2024)
Nowadays, issues related to children's academic achievement are something that parents are concerned about. Every effort is made to improve their performance at school. However, there are times when children become tired or bored due to the long time needed to study. In some case found at SMAN 1 Tambun where the intelligence level is good but the learning achievement at school is not so, aka the value is very standard or behaves lazily at school or even like it is difficult to socialize so that it tends to be individual. From this matter, the teachers finally think that is the influence on current learning achievement externally and internally on their students. Not to mention that children are very easy to make excuses, especially those related to stress either due to the demands of parents, little rest time, do not fit into the environment so that they get to the point that school is not important just a formality so as not to be reprimanded by parents or to be the same as most people. The high and low achievement motivation of students is always used as an indicator of the good and bad learning achievement of a student. With achievement motivation, students will be encouraged to learn and like certain subjects happily studying the subject. In this study using a sample of 110 students and researchers sampled class X students at SMAN 1 TAMBUN. The results of this study indicate that there is a positive and significant influence of peer support, authoritarian parenting and resilience on academic achievement.